Making visible the invisible : Metrical patterns, contrafacture and compilation in a Medieval Castilian Songbook - Rio Riande, María Gimena del (2015)
With the help of our databases we illustrate in this piece of work the possible contrafactures, common metrical and rhyming patterns, and cycles of poems in the antiquiores? corpus, and give an account of more complex definitions. The examples will also serve as an opportunity to cast our eyes again on the macro-microanalysis (Jockers, 2013; Jockers and Flanders, 2013; Liu, 2014) and data-text (Marche, 2012) debates in the field of literary studies and the concepts of close-distant reading (Moretti, 2013; Latour, 2014) and relate them to a subject of study that is interested in formal patterns (and not as much in content) and acquires new meaning when compared through large corpora: metrics.